Innovations dans les écoquartiers : quelques leçons pour la gouvernance de la transition énergétique - Stéphane La Branche (VertigO)
Efforts in the construction of ecodistricts are territorially based illustrations of the energy transition efforts more globally that include both energy efficiency and diversity objectives and methods. But these efforts meet obstacles (and accelerators) in achieving energy efficiency objectives and even more, energy diversity. These obstacles and issues are both technical and social in the large sense of the term since they include energy actors’ role in these efforts, which we call “socioenergy nodes”. I put forward, based on an empirical analysis, that both the challenges and the value-added of these projects are more closely related to their governance than to their technical aspects. They also go well beyond the specific case of ecodistrics and raise issues related to the general process of energy transition.